A second species of Humorolethalis Robinson, Li & Yeates, 2020 from Australia (Diptera: Asilidae: Brachyrhopalinae) - Daniels, Greg (Zootaxa, 2026)
Dasypogon analis Macquart, 1850 (= Dasypogon tasmanicus Koçak & Kemal, 2008 syn. nov.), is transferred to Humorolethalis Robinson, Li & Yeates, 2020. The type locality ‘Tasmanie’ as published by Macquart is considered to be incorrect and is more likely to be South East Queensland. A key is presented to distinguish Macquart’s species from the only other described species, H. sergius (Walker, 1849). The female is described and illustrated.